2015
DOI: 10.1016/j.eaef.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Design and testing of a nutrient mixing machine for greenhouse fertigation

Abstract: a b s t r a c tTo improve the efficiency and accuracy of water-nutrient mixing, a multi-channel fertigation machine was designed; the hardware includes a programmable logic controller (PLC), a touch system and multichannel sensors. A sectional forecast control algorithm based on the nutrient dilution model was proposed to control the fertigation machine. When the 100-fold concentrated nutrient solution was diluted by a factor of 20e200, the results showed that the standard deviations of the electrical conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In addition, scholars at home and abroad have proposed a large number of intelligent control algorithms to improve the control accuracy of the water-fertilizer ratio [5,6]. Sun G X et al [7] proposed a segmented predictive control algorithm based on the nutrient dilution model for the fertilization accuracy of multichannel fertilizer applicator, and the study showed that the multichannel water-nutrient mixing ratio obtained under the algorithm had high accuracy, but the system only detects the total conductivity and pH in the fertilizer path, and it cannot obtain the fertilization amount of different fertilizers. Bahat et al [8] proposed an intelligent control system to control the water-fertilizer ratio, which is a good control strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, scholars at home and abroad have proposed a large number of intelligent control algorithms to improve the control accuracy of the water-fertilizer ratio [5,6]. Sun G X et al [7] proposed a segmented predictive control algorithm based on the nutrient dilution model for the fertilization accuracy of multichannel fertilizer applicator, and the study showed that the multichannel water-nutrient mixing ratio obtained under the algorithm had high accuracy, but the system only detects the total conductivity and pH in the fertilizer path, and it cannot obtain the fertilization amount of different fertilizers. Bahat et al [8] proposed an intelligent control system to control the water-fertilizer ratio, which is a good control strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Back et al [8] investigated the variable-rate fertilizer applicators with an image-based application rate measurement system, which allows for measuring precisely the rate of granular fertilizers applied. Moreover, Sun [9] designed a multi-channel fertigation machine and proposed a sectional forecast control algorithm based on the nutrient dilution model to improve the efficiency and accuracy of the water-nutrient mixing. Furthermore, diverse end-market products for fertigation, including the NutriFlex, NutriFit, and NutriJet irrigation machines (Priva Company, De Lier, The Netherlands), Elgal-Agro system, automatic fertigation machine (Fertiga, Kfar Blum, Israel), and the MICO-MASTER series products (HARDIE IRRIGATION, Welshpool, UK), have been developed in this regard.…”
Section: Introductionmentioning
confidence: 99%